The Secrets of the Immortal Nicholas Flamel: The Magician - Book 2 - Scott, Michael 1959- (New York : Delacorte Press, 2008)
Fifteen-year-old twins Sophie and Josh Newman continue their magical training in Paris with Nicholas Flamel, Scatty, and the Comte de Sant Germaine, pursued by Doctor Dee and the immortal Niccolo Machiavelli.
Keywords: Flamel, Nicolas, -- d. 1418 -- Fiction; Machiavelli, Niccolò, -- 1469-1527 -- Fiction; Dee, John, -- 1527-1608 -- Fiction; Alchemy -- Fiction; Magic -- Fiction; Supernatural -- Fiction; Siblings -- Fiction; Twins -- Fiction; Paris (France) -- Fiction